(untitled) (ModaPalavra e-periódico, 2021)
By understanding the relationship between crochet crafts, fashion design and fashion communication, there is a possible and viable path for the future of sustainable fashion. The creation of new scenarios and dialogues between designers and crochet artisans, supported by fashion communication methodologies, allows the development of fashion design through social, ethical and sustainable structures, as well as the development in face of the problems of the fashion industry, offer an alternative to slow down and point to new forms of consumption. In this process, of acceptance and recognition of crochet crafts, as a design language, fashion communication tools and strategies must be properly understood. This article seeks to accomplish through classical literature, a dialogue between the three areas of knowledge, crochet crafts, fashion and communication design, particularly in regard to new possibilities and development of sustainable markets in fashion in the face of the sector’s challenges.